Recovery experiences: a bibliometric review and science mapping analysis - Mohamed, Rosmah; Han, Yao; Ali, Mass Hareeza; Raja Yusof, Raja Nerina (Inderscience Publishers, 2025)
The recovery experiences of employees have been examined over the past 17 years. A bibliometric analysis was performed to conduct an extensive examination of worldwide research patterns in this area. Using the Scopus database, 476 publications from 2007 to 2023 were searched. The study focused on examining the temporal distribution, top-performing journals, regions, organisations, authors, international and author collaborations and cited publications. Additionally, it delved into co-word and co-citation analyses. The scientific landscapes were displayed using the VOSviewer software. The results were discussed using performance analysis and visualisation map. The study gives a more complete picture of recovery experiences research and offers hints for future research in this area.